Thermal stratification in upper layang reservoir with particular reference to water quality and treatment - Mohd. Azraai Kassim, 1958-; Wan Azam Wan Hamid; Noor Salehin Md. Nor; National Seminar on Advances in Environmental Control Technology (2nd : 1995 : Kuala Lumpur)
07